Acute necrotizing encephalopathy associated with lymphoma-associated hemophagocytic lymphohistiocytosis: A case report and literature review - Sun, Wenqiang; Fu, Changchang; Zhu, Xueping (Frontiers in Oncology, 2022)
Damage associated with lymphoma-associated hemophagocytic lymphohistiocytosis (LA-HLH) to the central nervous system (CNS) is not uncommon. However, the combination of brain damage resembling acute necrotizing encephalopathy (ANE) is rarely reported. Herein, we introduce the diagnosis and treatment of a case of ANE associated with LA-HLH in our hospital and review the relevant literature. After treatment, the child was discharged with only dysarthria and decreased sucking ability. The child is discharged from the hospital for six months with regular follow-up. Disease in remission with no signs of recurrence. LA-HLH and ANE are related to cytokine storm. Therefore, early steroid application is essential for treating these diseases.